Consumption and its consequences - Miller, Daniel, 1954- (Cambridge : Polity, 2012)
This title brings together Miller's key writings on consumption, consumer capitalism and related topics.
What's wrong with consumption? -- A consumer society -- Why we shop -- Why denim? -- It's the stupid economy -- How not to save a planet.
Includes bibliographical references (p. [186]-201) and index.
Keywords: Consumption (Economics); Material culture